A New Strategy for the Treatment of Patients With Prolonged Impairment of Consciousness Using Xenon. Prospective Pilot Study - A. I. Shpichko; A. N. Kuzovlev; R. A. Cherpakov; N. P. Shpichko; O. A. Grebenchikov; A. K. Yevseyev; A. K. Shabanov; S. S. Petrikov (Неотложная медицинская помощь)
In addition to high mortality, craniocerebral injuries have another danger, a long rehabilitation period and a high percentage of disability with the development of cognitive impairment. This is primarily associated with the processes of neuroinflammation, which development, according to recent data, leads to a long-term impairment of consciousness. The anti-inflammatory effects of xenon inhalation anesthetic, which have been repeatedly shown in previous studies, have the potential to beneficially affect the level of consciousness in these patients by targeting key links of neuroinflammation.AIM OF STUDY To evaluate the effect of oxygen-xenon mixture inhalation on the level of consciousness recovery and the severity of spastic activity in patients after traumatic brain injury.MATERIAL AND METHODS A prospective randomized clinical trial of the effect of inhaled xenon sedation on the level of consciousness and spastic activity in patients with post-coma long-term impairment of consciousness was conducted. Patients were randomized into two equal groups. In group I (comparisons, n=15) (in addition to the standard treatment after a traumatic brain injury), each patient included in the study underwent 7 sessions of inhalation of an air-oxygen mixture with an oxygen content of at least 30 vol% for 30 minutes. In group II (study, n=15) (in addition to standard treatment), each patient included in the study inhaled an oxygen-xenon gas mixture (xenon content 30 vol%) for 7 days 1 time per day. Before and after the course of treatment (on the 7th day), patients were assessed using the CRS-R scale and the modified Ashworth scale.RESULTS The final evaluation included 12 patients from the comparison group and 12 patients from the study group. Three patients were excluded from each group as a result of critical incidents not related to the type of the therapy. In the comparison group on the 7th day, the level of consciousness was score 9 [7; 11] and did not differ statistically significantly from the baseline (p>0.05), which was score 8 [6; 10]. Spastic activity also did not change statistically significantly. In group II, the initial level of consciousness was 9 [7; 10], and on the 7th day — score 15 [12; 17], which was statistically significantly higher both in relation to the level of consciousness by the 1st day (p=0.021) within the group, and in relation to it on the 7th day in group I (p=0.038). When comparing spastic activity on the 1st and 7th days, we did not obtain a statistically significant difference in any of the groups.CONCLUSION Our method of xenon inhalation made it possible to have a beneficial effect on the level of consciousness of patients after traumatic brain injury, but this did not affect the final level of spastic activity in any way.